KLASIFIKASI KELAYAKAN PEGAWAI KONTRAK MENJADI PEGAWAI TETAP MENGGUNAKAN METODE NAIVE BAYES - Khoirudin, Muh. Rosyid; Hasbi, Muhammad; Widada, Bebas; Akhyar, Khoirul; Sandradewi, Kumaratih (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2024)
Employees are the most important asset in the ongoing activities and programs that have been designed by the foundation and the emergence of difficulties in determining the status of new staff at the foundation, because the manual system is still in effect, from written exams, oral exams and interviews. which allows the loss of files in testing and lack of objectivity in giving an assessment to employees. Therefore, this research was conducted to help determine the eligibility of foundation employees to be classified into "Eligible" and "Not Eligible" to be appointed as permanent employees of the foundation. The method implemented in this study uses the Naive Bayes classifier method in determining classification, in research testing using the Confussion Matrix validity testing method. The creation of a foundation employee classification system using the Naive Bayes method, which can determine the classification results based on the results of Eligible and not eligible to be appointed as permanent employees of the foundation. the test results obtained from the study used 50 data, with details of 35 as training data 15 training data obtained an accuracy of 86.7%. from here which shows that this program can be used as a reference in determining the eligibility status of permanent employees at the Smart Cendekia foundation.